Arctic region: Peary Arctic Club, 1898-1902, camp in Lincoln Sea - Peary, Robert E. (Robert Edwin), 1856-1920 (1898)
Camp at 84° 17' N. Lat. (April 21, 1902) http://www.matthewhenson.com/1909NPtrip/1910b.html